Global convergence in correlations among soil properties - Xie, Baicheng; Zhang, Chunxia; Wang, Guodong; Xie, Yingge (International Journal of Agricultural and Biological Engineering, 2020)
The correlations among major soil properties at a global scale are essential for explaining the global convergence of ecological processes in terrestrial ecosystems but have never been assessed. In this study, a global soil database was analyzed to determine whether correlations among soil properties were consistent and how such correlations varied among continents and land use types. Across the entire dataset, the electrical conductivity of soils increased significantly with increasing pH; additionally, the total nitrogen and cation exchange capacity increased significantly with increasing organic carbon content, while the organic carbon content and cation exchange capacity decreased significantly with increasing sand content in soil. The correlations between paired soil properties were consistent among continents and land use types. The slopes of the relationships, however, varied significantly by continent and land use type. The results indicated a global convergence of correlations among soil properties and variation in the slopes of specific relationships between paired soil properties among continents and land use types. Such consistent global correlations and different slopes of specific correlations can have important implications in explaining the global patterns of biogeochemical processes and can provide some basis for linking soil resources with ecological processes on a global scale.Keywords: continent, land use, organic carbon, electricity, pH, CECDOI: 10.25165/j.ijabe.20201303.4547Citation: Xie B C, Zhang C X, Wang G D, Xie Y G. Global convergence in correlations among soil properties. Int J Agric & Biol Eng, 2020; 13(3): 108–116.